Spectroscopic characterization of chemically modified porous silicon - GOUNKO, IOURI; MOORE, ALAN; PEROVA, TANIA (SPIE, 2003)
The discovery of room temperature photoluminescence in porous silicon has opened up a range of applications for this material in new areas such as optical, photodetector, photovoltaic, micromachine and sensors. For this reason there have been significant efforts in recent years directed at modification of silicon surfaces via formation of Si-C and Si-O-E (E = H, C, N) bonds on the silicon surfaces. However, research on bonding of metallorganic fragments to the silicon surface is scant. The main objectives of our work are to develop and investigate new ways of specific chemical bonding of selected metallorganic compounds to the Si surface and to prepare new types of silicon-based materials. New metallorganic composites have been developed on macro- and micro- porous silicon surfaces. The silicon surfaces have been effectively modified using inorganic and organometallic chemistry approaches. The work includes: (i) preparation and investigation of Cl-, HO-, and Cp- modified porous Si-surfaces; (ii) preparation and characterisation of iron oxide layerson porous silicon; (iii) characterization of metallorganic layers on porous silicon by FTIR, EDX and Scanning Electronic Microscopy (SEM). There are strong possibilities that those composite materials will have a wide range of applications in nano-technology and optoelectronics.
PUBLISHED
Keywords: Porous Silicon; Nanocomposites; IR spectroscopy